Regime shift tipping point in hare population collapse associated with climatic and agricultural change during the very early 20th century. (15th May 2021) - Reid, Neil; Brommer, Jon E.; Stenseth, Nils C.; Marnell, Ferdia; McDonald, Robbie A.; Montgomery, W. Ian
Abstract: Animal populations at northern latitudes may have cyclical dynamics that are degraded by climate change leading to trophic cascade. Hare populations at more southerly latitudes are characterized by dramatic declines in abundance associated with agricultural intensification. We focus on the impact of historical climatic and agricultural change on a mid‐latitude population of mountain hares, Lepus timidus hibernicus . Using game bag records from multiple sites throughout Ireland, the hare population index exhibited a distinct regime shift. Contrary to expectations, there was a dynamical structure typical of northern latitude hare populations from 1853 to 1908, during which numbers were stable but cyclic with a periodicity of 8 years. This regime was replaced by dynamics more typical of southern latitude hare populations from 1909 to 1970, in which cycles were lost and numbers declined dramatically. Destabilization of the autumn North Atlantic Oscillation (NAO) led to the collapse of similar cycles in the hare population, coincident with the onset of agricultural intensification (a shift from small‐to‐large farms) in the first half of the 20th century. Similar, but more recent regime shifts have been observed in Arctic ecosystems and attributed to anthropogenic climate change. The present study suggests such shifts may have occurred at lower latitudes more than a century ago during the very early 20th century. It seems likely that similar tipping points in the population collapse of other farmland species may have occurred similarly early but went undocumented. As northern systems are increasingly impacted by climate change and probable expansion of agriculture, the interaction of these processes is likely to disrupt the pulsed flow of resources from cyclic populations impacting ecosystem function. Abstract : Up to the beginning of the 20th century, numbers of hares shot throughout Ireland were stable but fluctuated in a roughly 8‐year cycle synchronous with a similar cycle in autumn weather. Thereafter, cycles disappeared in both the climate and hare numbers with the latter declining dramatically throughout the 20th century associated with agricultural change. The tipping point in the detected regime shift occurred decades before similar population collapses observed in other farmland species during the late 20th century – evidence of the impact of early global change on wildlife. ​